Productivity and Economic Growth in Switzerland 1991-2006 - Barbara Rudolf; Mathias Zurlinden (Swiss Journal of Economics and Statistics, 2010)
In this paper, we analyse the sources of economic growth in Switzerland during the period 1991-2006. The results suggest that labour input and capital input contribute 0.52 pp and 0.57 pp, respectively, to the average annual GDP growth of 1.44%. The remaining 0.35 pp represent growth in multi-factor productivity, which is calculated as a residual. The estimate of growth in multi-factor productivity is lower than in previous studies because our measure of labour input takes changes in labour quality into account. Changes in labour quality explain 0.39 pp of the 0.52 pp contribution from labour input.
Keywords: E31; E37; 330; Growth Accounting; Productivity; Capital services; Constant-quality labour